Left Pulmonary Artery Stenting for Left Pulmonary Artery Stenosis Following Patent Ductus Arteriosus Device Closure: Case Series and Review of the Literature - Víctor Molina; Mehdi Hadid; Joaquim Miró; Nagib Dahdah (Case Reports in Cardiology)
Percutaneous device occlusion is currently the standard of care for most cases of patent ductus arteriosus (PDA). Albeit infrequent, device-related left pulmonary artery (LPA) stenosis is a known complication of this procedure, occasionally requiring stent placement to relieve the obstruction. We present a series of four patients who required left pulmonary stenting after ductus arteriosus device closure. A review of the current evidence is presented.